2009
DOI: 10.1094/phyto-99-9-1070
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Host Range Variation of Ralstonia solanacearum Strains Entering North America

Abstract: Each year, large volumes of ornamental and food plant propagative stock are imported into the North America; occasionally, Ralstonia solanacearum is found systemically infecting this plant material. In this study, 107 new R. solanacearum strains were collected over a 10-year period from imported propagative stock and compared with 32 previously characterized R. solanacearum strains using repetitive polymerase chain reaction (rep-PCR) element (BOX, ERIC, and REP) primers. Additional strain comparisons were made… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 28 publications
2
37
0
5
Order By: Relevance
“…Adaptation to some particular hosts and capacity to induce latent infections in plant material may have been a key factor for dissemination (and a possible demographic bottleneck). Plant-mediated dissemination was mostly associated with banana, ginger and potato (Buddenhagen, 1986;Coutinho, 2005), and strains intercepted in global surveys on latently infected plant material were mostly of phylotype IIB, not of phylotype I (Norman et al, 2009). This contradiction can, however, be explained by the fact that this survey was largely performed on imports of South America, where IIB strains are prevalent.…”
Section: Discussionmentioning
confidence: 99%
“…Adaptation to some particular hosts and capacity to induce latent infections in plant material may have been a key factor for dissemination (and a possible demographic bottleneck). Plant-mediated dissemination was mostly associated with banana, ginger and potato (Buddenhagen, 1986;Coutinho, 2005), and strains intercepted in global surveys on latently infected plant material were mostly of phylotype IIB, not of phylotype I (Norman et al, 2009). This contradiction can, however, be explained by the fact that this survey was largely performed on imports of South America, where IIB strains are prevalent.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, genes or QTLs associated with BW-resistance were reported against non-characterized R. solanacearum strains, whereas strain-and phylotype-specific QTLs were reported for tomato. Among solanaceous-infecting R. solanacearum populations, phylotype I strains are the most prevalent clade found in most Asian eggplant production areas (Horita and Tsuchiya 2001;Ivey et al 2007;Jaunet and Wang 1999;Xu et al 2009) as well as in Africa (Mahbou Somo Toukam et al 2009), America (Ji et al 2007;Norman et al 2009;Sanchez Perez et al 2008), and the Caribbean ). In a previous study, we showed that phylotype I strains display different virulence patterns, called pathoprofiles, on a core collection of tomato, pepper and eggplant representative of the genetic diversity for resistance in these species (Lebeau et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The Bv2 strains presented in this study all grouped in the phylotype II branch, with one strain in the IIa subpopulation and all the others in the IIb subpopulation, corroborating the result of the multiplex PCR for phylotype determination (results not shown and Table 1). This result reflects the fact that strains from the same geographic origin (i.e., Asia, America, Africa, Indonesia) most likely share a common ancestor (Jeong et al 2007;Ji et al 2007;Norman et al 2009;Wicker et al 2007). The geographic isolation explains the population divergence.…”
Section: Discussionmentioning
confidence: 84%